Erratum: predictors of malignancy in pancreatic head mass: a prospective study - The Pan African Medical Journal (The Pan African Medical Journal, 2016)

(untitled)
This erratum corrects ''Predictors of malignancy in pancreatic head mass: a prospective study'' The Pan African Medical Journal. 2011;9:30.